3D DEM-FEM simulation of the flexible metal wheel–soil interaction in low gravity environments. (March 2023) - Zhu, Jianzhong; Zou, Meng; Shen, Yan; Cao, Hongtao; Chen, Zhen; Qi, Yingchun
To investigate the driving performance of the flexible metal wheel of the manned lunar rover in a low gravity environment, we established a 3D discrete element method (DEM)-finite element method (FEM) coupling simulation system. The wheel was modeled by FEM and the soil was modeled by DEM. Then, the direct shear tests were performed to verify the validity of the DEM contact parameters. Finally, the driving performance of the flexible metal wheels with different treads under low gravity conditions was studied, and the velocity field of soil particles under the wheels was observed. The results show that the sinkage of the flexible wheel is almost independent of gravity, while the torque and drawbar pull are significantly affected by gravity. Moreover, by comparing the driving performance of the wheel equipped with treads (WT wheel) and without tread (NT wheel), it is found that the tread have great effect on sinkage, torque, and drawbar pull to wheel weight ratio due to the differences in wheel-soil contact area. Also, through the observation of the particle velocity field under the wheel, it is found that the gravity and load also have significant effects on the movement of soil particles. This study provided a reliable method for studies on the interaction between the flexible wheel and soil in low gravity environments.